Terapi Hipnoquran Sebagai Upaya Mengurangi Trauma Perceraian Seorang Single Parent Di Desa Wonokerto Kecamatan Tekung Kabupaten Lumajang (Jurusan Bimbingan dan Konseling Islam, 2020)
The purpose of this research is to find out the process and outcome of hypnotic therapy in treating thetrauma of a single parent. This study uses a qualitative descriptive approach, while the type of research used is casestudies. Data collector techniques in the form of observations and interviews. The analysis used in this study is framinganalysis done by emphasizing certain parts, highlighting certain aspects. Here the media selection, linking andhighlighting events so that the meaning of the event is easier to touch and remember by the audience. As for the stepsor procedure of Hipnoquran as follows: (1) Pre-Induction Talk; (2) induction; (3) deepening; (4) suggestion; (5)Termination. The final results after the implementation of hypnotic therapy are conducted among others: (1) Theclient has already spit a sense of sadness, disappointment, anger, and heartache during the therapeutic process, onlythese symptoms will reappear if the client is faced with events relating to the event of traumatic; (2) Currently theclient is able to open a heart for a man who wants to be his life companion. The client's negative perspective on menhas changed after therapy; (3) Heart pounding and breathlessness no more when administering the third therapy